Job satisfaction of non- managerial employees a case study on “A-ZEIQ CONSULTANTS GmbH” - Abdullah, Chowdhury Rashid (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, 2021.